Answer:1/(3+x)=(1/3)
1
(1−(−x/3))
1/(3+x)=(1/3)1(1−(−x/3))
Use this fact that
1/(1−t)=
∑
∞
0
t
n
(∗)
1/(1−t)=∑0∞tn (∗)
where
|t|<1
|t|<1
. I mean take
t=−x/3
t=−x/3
and...
Note that
|−t|=|t|<1
|−t|=|t|<1
is the radius of convergence
Step-by-step explanation:
The answer is y=5x. to solve just plug in the x values into the equation for example 5(2) = 10 just like it says on the table. Hope this helps
Answer:
Soooo what's the question?
Step-by-step explanation:
Answer:
5*0.75= 3.75 he'll spend $3.75 on lunch every week.
Step-by-step explanation:
Answer:
all...
Step-by-step explanation: